The Costs of Bankruptcy: Chapter 7 Liquidation versus Chapter 11 Reorganization - BRIS, ARTURO; WELCH, IVO; ZHU, NING (Journal of Finance, 2006)
ABSTRACT Our paper explores a comprehensive sample of small and large corporate bankruptcies in Arizona and New York from 1995 to 2001. Bankruptcy costs are very heterogeneous and sensitive to the measurement method used. We find that Chapter 7 liquidations appear to be no faster or cheaper (in terms of direct expense) than Chapter 11 reorganizations. However, Chapter 11 seems to preserve assets better, thereby allowing creditors to recover relatively more. Our paper also provides a large number of further empirical regularities.